Inter-professional education unveiling significant association between asthma knowledge and inhaler technique - Basheti IA; Hamadi SA; Reddel HK (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Objectives: To explore whether an association exists between health care professionals' (HCPs) asthma knowledge and inhaler technique demonstration skills. Methods: HCPs' asthma knowledge and inhaler technique demonstration skills were assessed at baseline at an inter-professional educational workshop focusing on asthma medication use. Asthma knowledge was assessed via a published questionnaire. Correct inhaler technique for the three inhalers, the Accuhaler, Turbuhaler and pressurized Metered Dose Inhaler (pMDI) was assessed using published checklists. Results: Two hundred HCPs agreed to participate: 10 specialists (medical doctors specialized in respiratory diseases) (5%), 46 general practitioners (23%), 79 pharmacists (39%), 15 pharmacists' assistants (8%), 40 nurses (20%) and 10 respiratory therapists (5%). Backwards stepwise multiple regression conducted to determine predictors of HCPs' inhaler technique, showed that out of many independent variables (asthma knowledge score, profession, age, gender, place of work, years in practice and previous personal use of the study inhaler/s), asthma knowledge score was the only variable showing significant association with inhaler technique (R2=0.162, p<0.001). Conclusion: This study revealed significant associations between asthma knowledge and inhaler technique scores for all HCPs. Providing inter-professional workshops for all HCPs involved integrating education on asthma knowledge and practice of inhaler technique skills are looked-for.